2013
DOI: 10.9790/3021-03141015
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Vertical Electrical Sounding (VES) for Subsurface Geophysical Investigation around Bomo Area, Kaduna State, Nigeria

Abstract: Electrical resistivity investigation was carried out around Bomo area, Zaria, Kaduna state, in order to study the subsurface geologic layer with a view of determining the depth to the bedrock and thickness of the geologic layers. Vertical Electrical Sounding (VES) using Schlumberger array was carried out at fifteen (15) VES stations. ABEM terrameter (SAS 300) was used for the data acquisition. The field data obtained have been analysed using computer software (IPI2win) which gives an automatic interpretation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 0 publications
2
5
0
Order By: Relevance
“…This is because there is no much industrial as well as human activities in the control site when compared with the studied sites. In the present study, the concentration of nickel obtained is almost the same with that reported by Jatau et al, (2008) in water analysis from Kaduna metropolis, which was 0.28mg/l. Also, Abdulrahman et al, (2011) analysed for copper in ground water from Riyad and was found to be 0.07mg/l which is the same with that obtained in this research work, Ogbonna et al, (2011) obtained 0.08mg/l in water sample from Kano metropolis.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…This is because there is no much industrial as well as human activities in the control site when compared with the studied sites. In the present study, the concentration of nickel obtained is almost the same with that reported by Jatau et al, (2008) in water analysis from Kaduna metropolis, which was 0.28mg/l. Also, Abdulrahman et al, (2011) analysed for copper in ground water from Riyad and was found to be 0.07mg/l which is the same with that obtained in this research work, Ogbonna et al, (2011) obtained 0.08mg/l in water sample from Kano metropolis.…”
Section: Resultssupporting
confidence: 90%
“…This is as a result of industrial pollution is higher in the studied site more than that of the control site. In the present study, the concentration of iron obtained is almost the same with that reported by Jatau et al, (2008) in water analysis from Kaduna metropolis, which was in the range of 0.32-0.67mg/l. Also, Abdulrahman et al, (2011) analysed for iron in ground water from Riyad and was found to be 0.09mg/l which is lower than that obtained in this research work.…”
Section: Resultssupporting
confidence: 90%
“…Over the years, engineering studies and groundwater exploration are on the increase as a result of geophysical survey. This is made possible due to the swift advances in software development and associated numerical modelling solutions which have shown the way to the development of the present day technology [12][13][14]. Studies have shown that vertical electrical sounding (VES) and electrical profiling are the two ways by which electrical resistivity survey can be conducted [6,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The electrical geophysical survey method is the detection of the surface effects produced by the flow of electric current inside the earth. The electrical techniques have been used in a wide range of geophysical investigations such as mineral exploration, engineering studies, geothermal exploration, archeological investigations, permafrost mapping and geological mapping [4]. Using this method, depth and thickness of various subsurface layers and their water yielding capabilities can be inferred.…”
Section: Introductionmentioning
confidence: 99%